On Heat Conduction in Domains Containing Noncoaxial Cylinders. (25th March 2012) - Lukkassen, Dag; Meidell, Annette
Abstract : We consider heat conduction in domains containing noncoaxial cylinders. In particular, we present some regularity results for the solution and consider criteria which ensure the single valueness of the corresponding complex potential. Examples are discussed. In addition, we present some classes of cases where the parameters describing the solution are rational. Alternative ways of calculating the heat flux are also discussed.